American wilderness : a new history - Lewis, Michael L., 1971- (Oxford University Press, 2007)
Ch. 1. American Wilderness--An Introduction, Michael Lewis. Ch. 2. American Wilderness and First Contact, Melanie Perreault. Ch. 3. Religion "Irradiates" the Wilderness, Mark Stoll. Ch. 4. Farm Against Forest, Steven Stoll. Ch. 5. Natural History, Romanticism, and Thoreau, Bradley P. Dean. Ch. 6. The Fate of Wilderness in American Landscape Art: The Dilemmas of "Nature's Nation", Angela Miller. Ch. 7. Wilderness Parks and Their Discontents, Benjamin Johnson. Ch. 8. A Sylvan Prospect: John Muir, Gifford Pinchot, and Early Twentieth-Century Conservatism, Char Miller. Ch. 9. G